Selection of an appropriate generation IV nuclear reactor development program: A systems engineering approach - Aliperio, Mark Gino E. (Animo Repository, 2019)
Generation IV nuclear power plants are deemed to be an important source of baseload power for long-term goals. Currently, there are several designs but few will be deployed in the near future due to strategic, economic, and even political reasons. Such factors pose a challenge in selecting an ideal Generation IV technology to commit time and financial resources to. This study presents a systems approach to decision making for an appropriate Generation IV nuclear power plant program. A methodology commonly used in Systems Engineering projects, the Analytic Hierarchy Process, was applied to evaluate the survey results from expert opinions. As input to the decision analysis methodology, a set of selection criteria was developed and evaluated by nuclear power technology experts. Safety and Reliability emerges as the most important goal area, followed by Waste Management and Economics in terms of priority. Sodium fast cooled reactors appear to be the most competitive in the two most important goal areas while very high temperature reactors for economics. Furthermore, the results of this project can be used as reference for decision making and future development of Generation IV reactors aimed at advancing nuclear technology to meet future energy demands.